Feeding increasing concentrate to Tifton 85 hay ratios modulated rumen fermentation and microbiota in Nellore feedlot steers - Ribeiro, C. S. [UNESP]; Granja-Salcedo, Y. T. [UNESP]; Messana, J. D. [UNESP]; Neto, A. J. [UNESP]; Canesin, R. C.; Fiorentini, G. [UNESP]; Alarcon, M. F. F. [UNESP]; Berchielli, Telma Teresinha [UNESP] (Cambridge Univ Press, 2015)
The use of diets with increasing proportions of concentrate to fibre can ensure appropriate energy levels and result in greater efficiency in Nellore feedlot steers. It was hypothesized that higher proportions of concentrate in the diet of these Nellore steers may affect ruminal fermentation and microbiota as a consequence of ruminal pH reduction. The present study was conducted to evaluate the effect of diets with four different roughage (hay Tifton 85) : concentrate ratios on intake, digestibility, rumen fermentation and rumen microbiota of Nellore feedlot steers. Higher proportions of concentrate in the diet did not affect intake and digestibility of dry and organic matter. The concentration of N-NH3, total rumen volatile fatty acid, acetic (C2), butyric (C4), isobutyric, valeric and isovaleric acids, and microbial nitrogen did not differ among diets. However, increasing proportions of concentrate in the diet resulted in a linear reduction in average rumen pH and increased propionic acid (C3) concentration, resulting in lower relative C2 : C3. Bacterial population of Fibrobacter succinogenes, Ruminococus flavefaciens and Ruminococcus albus decreased in the rumen. However, bacteria that are consumers of lactic acid (Selenomonas ruminantium and Megasphaera elsdenii) and producers of lactic acid (Lactobacillus sp. and Streptococcus bovis) increased when animals were fed with high-concentrate diets. The total number of protozoa was similar for the different roughage : concentrate ratios. Protozoan counts were only influenced by diet for the genus Dasytricha. The findings point to diets with increasing concentrate to Tifton 85 hay ratios as inhibiting the growth of some cellulolytic bacteria and reducing fibre digestibility, and indicate Tifton 85 hay as a possible modulated rumen fermentation in the Nellore steer feedlot.